Cross-cultural gene− environment interactions in depression, post-traumatic stress disorder, and the cortisol awakening response: FKBP5 polymorphisms and childhood trauma in South Asia. (June 2015) - Kohrt, Brandon A.; Worthman, Carol M.; Ressler, Kerry J.; Mercer, Kristina B.; Upadhaya, Nawaraj; Koirala, Suraj; Nepal, Mahendra K.; Sharma, Vidya Dev; Binder, Elisabeth B.
Abstract Despite increased attention to global mental health, psychiatric genetic research has been dominated by studies in high-income countries, especially with populations of European descent. The objective of this study was to assess single nucleotide polymorphisms (SNPs) in the FKBP5 gene in a population living in South Asia. Among adults in Nepal, depression was assessed with the Beck Depression Inventory (BDI), post-traumatic stress disorder (PTSD) with the PTSD Checklist-Civilian Version (PCL-C), and childhood maltreatment with the Childhood Trauma Questionnaire (CTQ). FKBP5 SNPs were genotyped for 682 participants. Cortisol awakening response (CAR) was assessed in a subsample of 118 participants over 3 days. The FKBP5 tag-SNP rs9296158 showed a main effect on depressive symptoms (p = 0.03). Interaction of rs9296158 and childhood maltreatment predicted adult depressive symptoms (p = 0.02) but not PTSD. Childhood maltreatment associated with endocrine response in individuals homozygous for the A allele, demonstrated by a negative CAR and overall hypocortisolaemia in the rs9296158 AA genotype and childhood maltreatment group (p < 0.001). This study replicated findings related to FKBP5 and depression but not PTSD. Gene–environment studies should take differences in prevalence and cultural significance of phenotypes and exposures into account when interpreting cross-cultural findings.